Interleukin-18 and IL-18 Binding Protein - Dinarello, Charles; Novick, Daniela; Kim, SooHun; Kaplanski, Gilles (Frontiers in Immunology, 2013)
Interleukin-18 (IL 18) is a member of the IL 1 family of cytokines. Increasing reports have expanded the role of IL 18 in mediating inflammation in animal models of disease using IL 18 deficient mice, neutralization of IL 18 or deficiency in the IL 18 receptor alpha chain. Similar to IL 1β, IL 18 is synthesized as an inactive precursor requiering processing by caspase 1 into an active cytokine but unlike IL 1β, the IL 18 precursor is constitutively present in nearly all cells in healthy humans and animals. The activity of IL 18 is balanced by the presence of a high-affinity naturally occuring IL 18 binding protein (IL 18BP). In humans, disease increased disease severity can be associated with an imbalance of IL 18 to IL 18BP such that the levels of free IL 18 are elevated in the circulation. A role for IL 18 has been implicated in several autoimmune diseases, myocardial function, emphysema, metabolic syndromes, psoriasis, inflammatory bowel disease, hemophagocytic syndromes, macrophage activation syndrome, sepsis and acute kidney injury, although in some diseases, IL 18 is protective. IL 18 plays a major role in the production of interferon-g from natural killer cells. The IL 18BP has been used safely in humans and clinical trials of IL 18BP as well as neutralizing anti-IL 18 antibodies are in clinical trials. This review updates the biology of IL 18 as well as its role in human disease